2018
DOI: 10.3390/pharmaceutics10040170
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Oral Compound Pickering Emulsion Composed of Nanocrystals of Poorly Soluble Ingredient and Volatile Oils from Traditional Chinese Medicine

Abstract: In this study, an oral drug nanocrystals self-stabilized Pickering emulsion (NSSPE), which used nanocrystals of a poorly soluble ingredient from Puerariae Radix called puerarin as solid particle stabilizers and Ligusticum chuanxiong essential oil since the main oil phase had been developed to improve the oral bioavailability of puerarin. The appearance of emulsions, size and zeta potential of droplets, and content of puerarin in emulsified layer during a storage of six months at 4, 25, and 40 °C were investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 39 publications
2
34
0
Order By: Relevance
“…However, many of the bioactive ingredients of traditional Chinese Pharmaceutics 2020, 12, 216 2 of 18 medicine (TCM) are poorly soluble, which leads to low oral bioavailability and delivery problems. This makes the efficacies of TCM decrease or administration doses increase [13][14][15]. Consequently, oral formulations with improved absorption of Pur have attracted widespread attention.…”
Section: Introductionmentioning
confidence: 99%
“…However, many of the bioactive ingredients of traditional Chinese Pharmaceutics 2020, 12, 216 2 of 18 medicine (TCM) are poorly soluble, which leads to low oral bioavailability and delivery problems. This makes the efficacies of TCM decrease or administration doses increase [13][14][15]. Consequently, oral formulations with improved absorption of Pur have attracted widespread attention.…”
Section: Introductionmentioning
confidence: 99%
“…The C max reached up to 7.267 ± 0.432 mg/L, which is more than three times higher than that of water group. The relative bioavailability was calculated as 323%, which is higher than that of the previously reported NSSPE [ 23 ] and SMEDDS [ 24 ] methods.…”
Section: Resultsmentioning
confidence: 57%
“…Efforts have been devoted into the improvement of the solubility and bioavailability of Pueraria flavones. Zhang et al [ 23 ] developed an oral drug nanocrystal self-stabilized Pickering emulsion (NSSPE) and investigated the oral bioavailability of PUE NSSPE. The results showed that the C max of PUE was increased from 634.17 ng/mL to 3226.14 ng/mL.…”
Section: Introductionmentioning
confidence: 99%
“…A novel liquid Pickering emulsion with a unique composition and microstructure, i.e., drug nanocrystals self-stabilized Pickering emulsion (NSSPE) has been developed to orally deliver poorly water-soluble drugs. In NSSPE, nanocrystals of poorly water-soluble drugs, which acted as the therapeutic substance as well as the stabilizer of emulsion, were adsorbed at the oil-water interface, forming a unique core-shell structure with a core of oil saturated with drug and a shell of drug nanocrystals [ 1 , 2 ]. Consequently, NSSPE could significantly enhance the oral bioavailability of poorly water-soluble drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, NSSPE could significantly enhance the oral bioavailability of poorly water-soluble drugs. Pharmacokinetics studies showed NSSPE improved AUC of silybin and puerarin to 4.6 times and 2.6 times compared with crude material, respectively [ 1 , 2 ], suggesting great application potential for oral administration of poorly water-soluble drugs. NSSPE also has the higher drug loading and safety than traditional emulsions [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%